1986
DOI: 10.1136/thx.41.5.407
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nicotine concentration and the white blood cell count in smokers.

Abstract: The peripheral blood total white cell count is 20-25% higher in smokers than in non-smokers (for review see ref 1). Smoking probably causes the increase in white cell count. Thus the count is higher in those who smoke and inhale more,2 while a change in cigarette consumption is associated with a corresponding change in white cell count, and giving up smoking with a reduction in the count.3 Despite this evidence, the way in which smoking raises the white cell count is unknown. This study was conducted to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Our data show, for the first time, that low levels of chronic nicotine of relevance to nicotine exposure in moderate smokers (19) or patients undergoing NRT (20) significantly reduce the therapeutic efficacy of gemcitabine in PDAC in vitro and in vivo. The significantly higher concentrations of gemcitabine required to yield a 50% reduction in viable cells from both PDAC cell lines exposed for 7 days to nicotine and the significant decrease of gemcitabine-induced inhibition of xenograft development in nicotine treated mice identify the low nicotine concentrations used in the current experiments as highly effective in reducing the anti-tumorigenic effects of gemcitabine in PDAC.…”
Section: Resultsmentioning
confidence: 72%
“…Our data show, for the first time, that low levels of chronic nicotine of relevance to nicotine exposure in moderate smokers (19) or patients undergoing NRT (20) significantly reduce the therapeutic efficacy of gemcitabine in PDAC in vitro and in vivo. The significantly higher concentrations of gemcitabine required to yield a 50% reduction in viable cells from both PDAC cell lines exposed for 7 days to nicotine and the significant decrease of gemcitabine-induced inhibition of xenograft development in nicotine treated mice identify the low nicotine concentrations used in the current experiments as highly effective in reducing the anti-tumorigenic effects of gemcitabine in PDAC.…”
Section: Resultsmentioning
confidence: 72%
“…It is well established that current smokers are characterized by increased white blood cell (WBC) counts and increased tumor necrosis factor-α(TNF-α) [3,4]. However, the effects of smoking on the increase in WBC counts and TNF-α have not been separately investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Smokers usually exhibit an elevated peripheral white blood cell count, around 30% higher than that of nonsmokers (Friedman et al, 1973;Yeung & Buncio, 1984;Mili et al, 1991). It has been shown a significant relationship between the white blood cell count in smokers and the plasma concentration of nicotine (Taylor et al, 1986). It has been suggested that nicotine induced catecholamine release might be the mechanism for this effect (Friedman et al, 1973).…”
Section: Cell-mediated Immune Responsesmentioning
confidence: 99%